Mycorrhiza alters the profile of root hairs in trifoliate orange - Wu, Qiang-Sheng; Liu, Chun-Yan; Zhang, De-Jian; Zou, Ying-Ning; He, Xin-Hua; Wu, Qing-Hua (Mycorrhiza, 2016)
Root hairs and arbuscular mycorrhiza (AM) coexist in root systems for nutrient and water absorption, but the relation between AM and root hairs is poorly known. A pot study was performed to evaluate the effects of four different AM fungi (AMF), namely, Claroideoglomus etunicatum, Diversispora versiformis, Funneliformis mosseae, and Rhizophagus intraradices on root hair development in trifoliate orange (Poncirus trifoliata) seedlings grown in sand. Mycorrhizal seedlings showed significantly higher root hair density than non-mycorrhizal seedlings, irrespective of AMF species. AMF inoculation generally significantly decreased root hair length in the first- and second-order lateral roots but increased it in the third- and fourth-order lateral roots. AMF colonization induced diverse responses in root hair diameter of different order lateral roots. Considerably greater concentrations of phosphorus (P), nitric oxide (NO), glucose, sucrose, indole-3-acetic acid (IAA), and methyl jasmonate (MeJA) were found in roots of AM seedlings than in non-AM seedlings. Levels of P, NO, carbohydrates, IAA, and MeJA in roots were correlated with AM formation and root hair development. These results suggest that AMF could alter the profile of root hairs in trifoliate orange through modulation of physiological activities. F. mosseae, which had the greatest positive effects, could represent an efficient AM fungus for increasing fruit yields or decreasing fertilizer inputs in citrus production.
Keywords: symbióza; Mycorrhizae; biomasa; Plant Shoots; semenáček; Glucose; Glomeromycota; Biomass; Citrus; výhonky rostlin; Root hairs; Plant Roots; Soil Microbiology; Soil; kořeny rostlin; MeJA; Seedlings; Mycorrhiza; Poncirus; půdní mikrobiologie; Symbiosis; IAA; půda; mykorhiza